Leptin inhibits 4-aminopyridine– and pentylenetetrazole-induced seizures and AMPAR-mediated synaptic transmission in rodents - Lin Xu; Nicholas Rensing; Xiao-Feng Yang; Hai Xia Zhang; Liu Lin Thio; Steven M. Rothman; Aryan E. Weisenfeld; Michael Wong; Kelvin A. Yamada (The Journal of Clinical Investigation, 2007)
Leptin is a hormone that reduces excitability in some hypothalamic neurons via leptin receptor activation of the JAK2 and PI3K intracellular signaling pathways. We hypothesized that leptin receptor activation in other neuronal subtypes would have anticonvulsant activity and that intranasal leptin delivery would be an effective route of administration. We tested leptin’s anticonvulsant action in 2 rodent seizure models by directly injecting it into the cortex or by administering it intranasally. Focal seizures in rats were induced by neocortical injections of 4-aminopyridine, an inhibitor of voltage-gated K+ channels. These seizures were briefer and less frequent upon coinjection of 4-aminopyridine and leptin. In mice, intranasal administration of leptin produced elevated brain and serum leptin levels and delayed the onset of chemical convulsant pentylenetetrazole-induced generalized convulsive seizures. Leptin also reduced neuronal spiking in an in vitro seizure model. Leptin inhibited α-amino-3-hydroxy-5-methyl-4-isoxazole proprionic acid (AMPA) receptor–mediated synaptic transmission in mouse hippocampal slices but failed to inhibit synaptic responses in slices from leptin receptor–deficient db/db mice. JAK2 and PI3K antagonists prevented leptin inhibition of AMPAergic synaptic transmission. We conclude that leptin receptor activation and JAK2/PI3K signaling may be novel targets for anticonvulsant treatments. Intranasal leptin administration may have potential as an acute abortive treatment for convulsive seizures in emergency situations.
Issue version published: January 2, 2008